CCR7 Has Potential to Be a Prognosis Marker for Cervical Squamous Cell Carcinoma and an Index for Tumor Microenvironment Change - Tian, Wei-Jie; Feng, Peng-Hui; Wang, Jun; Yan, Ting; Qin, Qing-Feng; Li, Dong-Lin; Liang, Wen-Tong (Frontiers in Molecular Biosciences, 2021)
The tumor microenvironment (TME) has an essential role in the development of cervical squamous cell carcinoma (CSCC); however, the dynamic role of the stromal and immune cells is still unclear in TME. We downloaded data from The Cancer Genome Atlas (TCGA) database and applied ESTIMATE and CIBERSORT algorithms to measure the quantity of stromal and immune cells and the composition of tumor-infiltrating immune cell (TIC) in 253 CSCC cases. The protein-protein interaction (PPI) network and Cox regression analysis presented the differentially expressed genes (DEGs). Then, C-C chemokine receptor type 7 (CCR7) was screened out as a prognostic marker by the univariate Cox and intersection analysis of PPI. Further analysis showed a positive correlation between the expression of CCR7 and the survival of CSCC patients. The result of the Gene Set Enrichment Analysis (GSEA) of genes in the high CCR7 expression group displayed a predominant enrichment in immune-related pathways. An enrichment in metabolic activities was observed in the low CCR7 expression group. CIBERSORT analysis showed a positive correlation between Plasma cells, CD8+ T cells, and regulatory T cells and the CCR7 expression, suggesting that CCR7 might play a crucial role in maintaining the immunological dominance status for TME. Therefore, the expression level of CCR7 might help predict the survival of CSCC cases and be an index that the status of TME transitioned from immunological dominance to metabolic activation, which presented a new insight into the treatment of CSCC.